Sanojen luonto Kirjoituksia omaehtoisen ilmaisun poetiikasta ja ympäristöistä - Sykäri, Venla; Mäkelä, Heidi H; Kallio, Kati (Suomalaisen Kirjallisuuden Seuran Toimituksia, 2023)
In recent decades, the focus of Folklore Studies has shifted from analysing the products of oral traditions as texts to examining the ways in which people use and produce these items, and the areas of study have broadened to include vernacular cultures and genres in diverse verbal and material forms. As evident from the introduction and twelve chapters of this collection, these interests are today shared by several disciplines that cooperate in the area of cultural studies. This book provides insights into current questions about the "nature" of words: it discusses both the inherent essence of vernacular expression and how that essence is tied to various genre-ecological, performative, and material environments. The chapters include studies on the poetics, form, function, performance, and composition of traditional and new vernacular forms, including explorations of hybridity, materiality, and change, as well as critical examinations of archival practices and publication processes.